2022
DOI: 10.1002/dc.24970
|View full text |Cite
|
Sign up to set email alerts
|

Malignant granular cell tumors: Combining cytological and pathological findings for a definitive diagnosis

Abstract: Malignant granular cell tumors (GCTs) account for less than 2% of all GCTs and mainly occur in the deep soft tissue of the thigh or trunk. Malignant GCTs are highly aggressive tumors with high rates of recurrence and metastasis. In this brief report, we describe a rare case of malignant GCT in a 64‐year‐old Japanese man who presented with a 14 × 20 cm mass in the left inguinal region. The cytologic findings of fine‐needle aspiration (FNA) revealed atypical epithelial‐like granular cells with granular substance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In 2018, Pareja et al performed whole exome sequencing of benign and malignant GCTs and identified inactivating mutations of ATP6AP1 and ATP6AP2 in 49-74% [92,[97][98][99]. In vitro inactivation impairs the V-ATPase gene complex in Schwann cells and leads to the formation of GCTs [97].…”
Section: Granular Cell Tumorsmentioning
confidence: 99%
“…In 2018, Pareja et al performed whole exome sequencing of benign and malignant GCTs and identified inactivating mutations of ATP6AP1 and ATP6AP2 in 49-74% [92,[97][98][99]. In vitro inactivation impairs the V-ATPase gene complex in Schwann cells and leads to the formation of GCTs [97].…”
Section: Granular Cell Tumorsmentioning
confidence: 99%
“…This tumor is categorized as benign soft tissue overgrowth and in less than 2 % of the cases, malignancy occur [ 2 ]. The peak age of the disease presentation is in fifties with predominancy between 30 and 50 years old [ 3 ]. The tumor most commonly affects mucosal soft tissue like tong, oral cavity, respiratory tract and many other rare sites.…”
Section: Introductionmentioning
confidence: 99%
“…Pleomorphic tumor cells with multiple mitoses and projecting nucleoli are cancerous cells. In more than half of the cases, regions of necrosis and calcifications can be seen (Enomoto et al., 2022). Medullary carcinoma : 5% of all cases of invasive breast cancer are caused by this subtype.…”
Section: Introductionmentioning
confidence: 99%